English literary studies: including Islamic perspectives in pedagogy and practice - Hasan, Md. Mahmudul (The International Institute of Islamic Thought, 2015)
Proponents of the integration of Islam into English literary studies seek, by way of presenting Islamic worldviews in relation to the life-worlds that English texts presumably promote, to inform (Muslim) students and practitioners of the subject about possible untoward influences in order to help them withstand cultural captivity and lifestyle effects. This is part of the wider concept of integrating Islam into human knowledge, which functions across a broad range of subject areas and generally refers to a method of looking at academic disciplines from Islamic perspectives and enlightening the reader about relevant Islamic teachings. Based on this theoretical premise, in this article I focus on the need for and three important ways of teaching English literature: inculcating Islamic/moral values, identifying predominant themes and ideas inherent in literary texts and looking at them from Islamic perspectives, and reforming the curriculum.